Modeling trophic structure and ecosystem functioning of the Small Fish-dominated largest lake of Bangladesh - Mondal, Debashis Kumar; Yin, Chengjie; Zhao, Kangshun; Farooq, Muhammad; Halim, Md Abdul; Wang, Ruilong; Xu, Jun (John Wiley and Sons Ltd, 2026)
Ecosystem modeling is becoming increasingly important, as it reveals how energy flows and species interactions shape ecosystem stability, resilience, and the sustainability of fisheries. However, model-based ecosystem studies are scarce for the Kaptai Lake (KL) of Bangladesh. Therefore, a mass-balanced trophic model was built to illustrate the trophic structure and ecosystem features of KL. The model outputs indicated that the apex predator, Catfish (TL-3.364), occupied the top trophic niches, while the overabundant (B: 3.264 t/km2) Clupeid (TL-2.56) dominated the lower trophic level in the food web. The higher values of ecotrophic efficiency (> 0.5) for most of the groups indicate heavy fishing pressure. The ecosystem is Phytoplankton-based, where two core food chains that make up the majority of the food web are the Detritus (35.12%) and primary production (64.88%). The mixed trophic impact plot revealed a substantial positive effect of Detritus and Phytoplankton on the majority of the fish groups. Clupeids displayed a negative effect on most of the fish groups, indicating a lack of major predators of this group. In the KL ecosystem, Catfish and Phytoplankton were the key predator and producer groups, respectively. The network analysis indicates that the KL is a developing ecosystem with moderate system maturity, as evidenced by total primary production and respiration ratio (2.034), total primary production and biomass ratio (71.764), and Finn Cycling Index (5.627%). The low connectance index (0.426) indicates that the food web is still linear rather than a web-like structure and thereby vulnerable to external influences. Besides, the ever-increasing trend of Clupeid and declination of large fish populations indicates that the KL ecosystem may encounter severe consequences in the future. Consequently, ecosystem-based management interventions have been proposed that will help to restore food web integrity, recover vulnerable species and ensure long-term sustainability of fisheries in this lake.